Cerebellar Ataxia, An Unusual Neurological Manifestation of Coeliac Disease- A Case Study (Bangladesh Journal of Neuroscience, 2016)
Coeliac disease was considered as a gluten sensitive enteropathy but now due to its wide clinical presentation is considered as multisystem autoimmune disorder. Ataxia with peripheral neuropathy is a rare manifestation of gluten sensitivity. The presence of glutenrelated immune markers in normal population however complicates the reliable diagnosis of gluten related neurological disorders and clinical improvement on gluten free diet can serve as a diagnostic tool for this disease. We report a case of sporadic progressive cerebellar ataxia with peripheral neuropathy with positive anti tissue transglutaminase (antitTG) antibodies and subtotal villous atrophy in duodenal biopsy. This case highlights an important diagnostic and therapeutic principle in management of late onset idiopathic ataxia.Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 43-46